Effect of Gross Profit Margin and Dividend Policy on Stock Price (Case Study of Food and Beverage Companies Listed on the IDX for the 2016-2021 Period) - Nur, Latief Z.; Riyadi, Wulan; Hernita, Nita (Journal of International Conference Proceedings, 2023)
In addition to rising demand for these products, an increasing number of financiers are eyeing the food and beverage business as a promising place to put their money. The value of the stock price is still the prima donna and the benchmark for them to determine the value of the investment they will take. The purpose of this research is to analyze the 2016-2021 performance of the IDX food and beverage sector in relation to gross profit margin and dividend. Forty food and beverage companies from the Indonesia Stock Exchange (IDX) were included in the study population. The sample used is company financial data. Using purposive sampling technique, 7 food and beverage companies with an observation period of 6 years (7x6=42) meet the criteria to be sampled in this study, so that a total sample of 42 financial data is obtained. which was sampled. Model feasibility and hypothesis testing, as well as the more traditional assumption test, are among the analytic methods employed. Based on the findings of this research, the Gross Profit Margin has no significant impact on stock prices for food and beverage businesses listed on the IDX during the 2016-2021 period, but the Dividend Policy has a positive and significant impact on stock prices during the same time period.